Tratamento de efluentes da indústria textil por coagulação e floculação utilizando polímeros naturais - Couto Júnior, Osório Moreira (2011)
The effluents of industrial screen printers, in general, contain debris removed from the clothes, and substances added, due to the direct application and fixation of dyes / pigments in the tissue, which are usually treated by physical and chemical processes of coagulation / flocculation and sedimentation. The chemical coagulant, aluminum sulfate is widely used in the treatment of textile effluents, due to good performance in the coagulation of colloidal particles and their low cost of implementation. However, this reagent chemical is not biodegradable and can pose serious risks to human health, depending on the concentration that is present in the water. Many of the effluent treatment has been developed and investigated by adopting the use of natural coagulants, since they have advantages over chemical coagulants, mainly due to biodegradation and low production of sludge waste. However, this study tests were performed coagulation/flocculation and sedimentation, in order to optimize the treatment of effluent from an industrial stamping, using chemical coagulant, aluminum sulfate and natural coagulants: Tannin and Moringa oleifera Lam. The tests were performed on apparatus jar test, varying the times of mixtures, sedimentation and concentration of coagulants. The samples were subjected to an initial period of rapid mixing (95 rpm), then blend slowly (35rpm) and rest for sedimentation. After coagulation / flocculation and sedimentation, the supernatants were transferred to other containers for later analysis. Raw and treated effluents in the printing collections were made and characterized with the same parameters for the tests performed in coagulation / flocculation, appearing always in high quantities in terms of organic matter expressed as COD. During tests of alkalinity, acidity, color, BOD5, COD, metals, pH, solids and turbidity. The optimal concentrations found were 400 mg /L, 600 mg /L and 2500 mg /L for Tannin, aluminum sulfate, and Moringa oleifera Lam, respectively. It was observed that treatment using the tannin was the most efficient removal of 99.17% reaching Color, 99.65% of Turbidity, 92.72% of BOD5, COD 94.81%, 47.85% Solids Total, and 96.67% of total suspended solids over the effluent. Among all the metal removed, it appears that the metals mercury and manganese had a greater than 60% removal by coagulants and removals of less than 30% were found only for chromium and silver, except for this Tannin, who achieved a higher removal. It can be concluded that the tannin showed the best results in terms of parameters investigated and lower economic costs in relation to chemical coagulant, aluminum sulfate, allowing savings of up to 22% per month.